COMPARISON BETWEEN IMMEDIATE AND DELAYED LOADING IN THE ALL-ON-4 PROTOCOL FOR ATROPHIC MAXILLAE - Marques, Sergio Augusto Rodrigues; Rodrigues, Durvalina Brito Ferreira; de Jesus, Joyce Oliveira Miranda; de Azevedo Filho, Afonso Ponte; Pereira, Alysson Esper; Bonfim, Ana Clara Carvalho; da Silva Júnior, José; Penteado, Gabriell Mafuz; Vitale, Marcelo; Borges, Kayole Alves Landim; Galani, Gabriel Marchiori; de Morais, Francielly Fernandes Pereira; et al. (Seven Editora, 2025)
Oral rehabilitation of patients with atrophic maxillae represents a clinical challenge in implant dentistry due to the limited bone availability for the placement of conventional implants. Although the All-on-4 protocol is widely used as a predictable and minimally invasive alternative, controversies remain in the literature regarding the ideal timing for prosthetic loading. This study aimed to analyze and compare scientific evidence published over the past ten years on the effectiveness of immediate and delayed loading protocols applied to the All-on-4 concept in atrophic maxillae. This is a narrative literature review conducted between September and November 2025 in the PubMed, SciELO, SpringerLink, MDPI, and Research, Society and Development Journal databases, using descriptors defined by MeSH and DeCS in both Portuguese and English. Original articles, systematic reviews, and clinical reports published between 2015 and 2025 comparing both loading protocols were included. Data were analyzed descriptively and comparatively, focusing on implant survival rates, marginal bone loss, and patient satisfaction. The results showed high implant survival rates (93.8%–99.3%) and mean marginal bone loss ranging from 0.8 to 1.5 mm, with high patient satisfaction in both protocols. It was concluded that both immediate and delayed loading are safe and effective approaches, and the choice of protocol should be individualized according to the patient’s clinical conditions. The findings contribute to improving treatment planning and evidence-based clinical practice in implant dentistry.DOI: https://doi.org/10.56238/sevened2025.037-047